Development of internally-calibrated, direct detection millimeter-wave radiometers to improve remote sensing of wet tropospheric path delay - Hadel, Victoria D., author; Reising, Steven C., advisor; Kangaslahti, Pekka, committee member; Notaros, Branislav, committee member; Van Den Heever, Susan, committee member (Colorado State University. Libraries, 2015)
Satellite ocean altimeters measure the sea surface height by emitting a radar pulse and measuring the time for it to propagate to the surface, bounce off and return to the satellite. Assuming speed-of-light propagation, the sea surface height can be determined. However, water vapor in the atmosphere, which is highly variable both temporally and spatially, reduces the propagation speed of these radar signals, in turn increasing the round-trip radar propagation time, leading to substantial errors in the sea surface height estimation. This delay in the arrival time of radar pulse returns is referred to as wet-tropospheric path delay. Past and current satellite ocean altimeters include nadir-viewing, co-located 18-34 GHz microwave radiometers to measure wet-tropospheric path delay with a precision of 1 cm. However, due to the large antenna footprint sizes at these frequencies, the accuracy of wet path retrievals is substantially degraded within 40 km of coastlines, and retrievals are not provided over land. Because footprint diameter is directly proportional to wavelength for the same antenna aperture size, a viable approach to improve their capability is to add wide-band millimeter-wave window channels in the 90-175 GHz band, thereby achieving finer spatial resolution for a fixed antenna size. To address this need, an internally-calibrated, wide-band, cross-track scanning airborne microwave and millimeter-wave radiometer has been collaboratively developed between Colorado State University (CSU) and Caltech/NASA's Jet Propulsion Laboratory (JPL). This airborne radiometer, referred to as the High Frequency Airborne Microwave and Millimeter Wave Radiometer (HAMMR) includes microwave channels at 18.7, 23.8, and 34.0 GHz at both Quasi-H and Quasi-V polarizations, millimeter-wave window channels at 90, 130, and 168 GHz, as well as temperature and water vapor sounding channels near the 118 and 183 GHz absorption lines, respectively. Since this instrument also serves as a prototype for potential future Earth science missions, substantial effort has been devoted to minimizing the mass, size and power consumption of the radiometer. Preliminary airborne measurements of the HAMMR demonstrate the reliable and robust operation of the millimeter-wave window and sounding channels on an airborne platform, as well as the improvement in spatial resolution that they provide, over that of the traditional microwave channels.
Keywords: millimeter wave; remote sensing; microwave; wet path delay; radiometers